Biocontrol activity of endophytic bacteria from cocoa against Phytophthora sp. and Colletotrichum sp. - Grace Wijaya; Agustin Krisna Wardani; Deden Eris (Menara Perkebunan, 2023)
Cocoa (Theobroma cacao L.) and chili pepper (Capsicum annuum L.) are commonly cultivated by farmers, and in some cases, both crops are grown together in intercropping systems. The main pathogen infected cocoa is the Phytophthora sp. fungus, which causes fruit rot, stem cancer, and leaf blight, while Colletotrichum sp. causes anthracnose in chili pepper plants. The ability of endophytic bacteria to inhibit the growth of fungi and bacterial pathogens is well known. In this study, the biocontrol ability of endophytic bacteria against fungal pathogens was tested, and a biocontrol preliminary test was also observed by examining their potential inhibition on Chromobacterium violaceum called antiquorum sensing test. Endophytic bacteria were isolated from cocoa plants, while Phytophthora and Colletotrichum were isolated from cocoa and chili pepper plants that showed symptoms of fruit rot and anthracnose. A total of 34 endophytic bacterial isolates were successfully obtained, with 10 isolates from leaves (DK), 12 isolates from branches (RK), and 12 isolates from roots (KA) of cocoa plant ICCRI 4. Sixteen isolates showed quorum sensing ability, which AHL degradation index ranging from 0.44 – 1.56. Antagonistic tests showed that 11 out of 16 isolates had strong antibiosis against Phytophthora sp., with inhibition zones ranging from 0.6-1.35 cm. Meanwhile, 10 out of 16 isolates had strong antibiotics against Colletotrichum sp., with clear zones ranging from 0.6 – 1.1 cm. The three best endophytic bacterial isolates that had a combination of antiquorum sensing ability on C. violaceum and biocontrol against Phytophthora sp. and Colletotrichum sp. were RK 11, KA 1, and KA 8. [Keywords: antagonist, ahl lactonase, plant beneficial microorganism]